Evolutionary genomics of filamentous fungi - Khaldi, Nora (Trinity College (Dublin, Ireland). Department of Genetics, 2008)
Filamentous fungi are important producers of secondary metabolites (SMs), together with plants and bacteria. While some SMs are toxic to humans, animals or plants, many others are beneficial. The discovery that the genes for each SM biosynthesis pathway tend to be physically clustered into a single locus in the genomes of filamentous fungi raises many evolutionary questions such as why, where and how do these clusters emerge? In this thesis I investigate some evolutionary questions about the origins of SM gene clusters, using the fumonisin cluster of Fusarium verticillioides and the Acel cluster of Magnaporthe grisea as models. I show that the fumonisin cluster was formed de novo in a recent ancestor of F. verticillioides', other filamentous fungi including the closely related F. oxysporum have orthologs of many of the genes, but these genes are not physically clustered. A different mechanism was found to underlie the formation of the Acel cluster: in this case, both duplication of a pre-existing cluster and horizontal gene transfer were involved.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin